la participación del trabajador social en el proyecto adulto mayor del gad municipal del cantón arenillas 2023. - Romero Sanchez, Maria Elena; Sanmartin Correa, Gissella Karolina (Machala, 2024)
Social Work in the care of older adults is of vital importance because it marks their welfare and quality of life during their old age. The term "senior citizen" refers to any person whose age is equal to or greater than 65 years. The exclusion and isolation of the elderly by family members increases the need to intervene in different areas to improve their quality of life and restore their rights, enforcing the law. Based on this, social projects aimed at this population are carried out, which must provide the necessary attention to guarantee prevention and the restitution of rights, in addition to strengthening their biological, psychological and social development. The objective of this degree work is to identify the participation of the social worker during the development of the Senior Citizen Project of the Arenillas Municipal Government. Within the epistemological foundation, it was considered to use the person-centered model, being the older adult responsible for making decisions together with the professional. In addition, as theoretical support for the research, they collected important and necessary data to learn about the intervention of the Social Work professional with older adults, the social diagnosis, the different support networks, the violation of rights and the family support plan. As legal regulations, the Constitution of the Republic of Ecuador establishes the rights designated to this priority group, as well as the duties of governmental and non-governmental institutions in caring for the elderly. On the other hand, the Organic Law for the Elderly (LOPAM) seeks to protect the physical and moral integrity of this group of people, in addition to guaranteeing and protecting their rights in the different areas of society. The research is of mixed approach, being the survey and the interview guide the necessary instruments to collect the information, generating a diagnosis based on the interpretation of data, being the attention deficit the main problem that arises through the Social Work professional, so it is necessary to develop an action plan to encourage the hiring of a professional exclusively for the senior project. Prior to the implementation of the intervention plan, it was evident that the canton authorities and professionals of the social welfare department were confused about the role of the social promoter and the social worker in the care of this priority group, assuming that both professionals fulfilled the same function. Therefore, with the sensitization project on the professional role of the social worker and the 10 elaboration of the respective work instructions, we sought to promote and highlight the role of the professional in the care of the elderly, knowing the benefits obtained by the social welfare department and the users of the project. In addition, with the preparation and delivery of the work instructions such as: social entry form, social form for home visits, social report and road map, the need to consider the professional to be part of the group of professionals in charge of caring for the elderly was encouraged, having the necessary instructions for its application.
El Trabajo Social en la atención a los adultos mayores es de vital importancia debido a que marca su bienestar y calidad de vida durante su vejez. Se considera el término adulto mayor a toda persona cuya edad es igual o mayor a 65 años. La exclusión y aislamiento del adulto mayor por parte de los familiares, acrecienta la necesidad de intervenir en las diferentes áreas para mejorar su calidad de vida y restituir sus derechos, haciendo valer lo establecido por la ley. En base a ello se realizan proyectos sociales dirigidos a esta población, los cuales deben proveer la atención necesaria para garantizar la prevención y la restitución de derechos, además de fortalecer su desarrollo biológico, psicológico y social. El presente trabajo de titulación tiene por objetivo identificar la participación del trabajador social durante el desarrollo del Proyecto Adulto Mayor del GAD Municipal del Cantón Arenillas. Dentro de la fundamentación epistemológica, se consideró utilizar el modelo centrado en la persona, siendo el adulto mayor responsable de tomar las decisiones en conjunto con el profesional, asimismo, como sustento teórico de la investigación recopilaron datos importantes y necesarios para conocer sobre la intervención del profesional en Trabajo Social con adultos mayores, el diagnóstico social, las diferentes redes de apoyo, la vulneración de derechos y el plan de apoyo familiar. Como normativa legal, la Constitución de la Republica del Ecuador, establece derechos designados a este grupo de atención prioritaria además de los deberes de las instituciones gubernamentales y no gubernamental al atender a los adultos mayores. Por otra parte, la Ley Orgánica de las Personas Adultas Mayores (LOPAM) busca proteger la integridad física y moral de este grupo de personas, además de garantizar y amparar sus derechos en las diferentes áreas de la sociedad. La investigación es de enfoque mixto, siendo la encuesta y la guía de entrevista los instrumentos necesarios para recabar la información, generando un diagnóstico en base a la interpretación de datos, siendo el déficit de atención el problema principal que surge a través del profesional de Trabajo Social, por lo que es necesario el desarrollo de un plan de acción para incentivar la contratación de un profesional exclusivo para el proyecto adulto mayor. Previo a la aplicación del plan de intervención, se evidenció la confusión de las autoridades del cantón y profesionales del departamento de bienestar social, sobre el papel que cumple el promotor social y el trabajador social en la atencion a este grupo prioritario, asumiendo 8 que ambos profesionales cumplían la misma función, por lo que con el proyecto de sensibilización sobre el rol profesional del trabajador social y la elaboración del respectivo instructivo de trabajo, se buscó promover y resaltar el papel que cumple el profesional en la atención a los adultos mayores, conociendo los beneficios que obtiene el departamento de bienestar social y los usuarios del proyecto, además, con la elaboración y entrega del instructivo de trabajo como: ficha social de ingreso, ficha social para visita domiciliaria, informe social y hoja ruta, se incentivó la necesidad de considerar al profesional a que forme parte del grupo de profesionales encargados de realizar la atención al adulto mayor, teniendo el instructivo necesario para su aplicación.
Keywords: TRABAJO SOCIAL; ADULTO MAYOR; DISCAPACIDAD; INTERVENCION